Egocentric social network routing in MANET. (2015) - Jang, HungChin; Lee, PeiHsuan
This research gears towards social aware assisted transmission based on trusty nodes in MANET. In this paper, social network analysis techniques are employed to analyse the relationship among users to select appropriate node for data forwarding. We propose an egocentric social network routing (ECSNR), which considers those neighbour nodes of either social aware or nonsocial aware nodes within its communication range for data forwarding. ECSNR uses degree centrality, betweenness centrality, interest similarity and friend diversity to accelerate data transmission and enhance successful data delivery. Besides, ECSNR has builtin redundant plan for overloaded nodes. The plan uses candidate list, recommended list and interestsimilar list to help select alternative nodes without wasting time in recalculating new delivery path. ECSNR is compared with SANE (Mei et al., 2011) through simulations. Simulation results show that ECSNR outperforms SANE in packet delivery ratio, endtoend delay and average hop count.